Perbedaan Depresi pada Pasien Asma Persisten dengan Pasien PPOK di RSUD Dr. Moewardi - Fahmi, Arum Alfiyah; Setijadi, Ana Rima; Sumardiyono, . (Nexus Kedokteran Klinik, 2013)
Background: Asthma and COPD are most pulmonary chronic disease. Recurrence dispnea attack in both can trigger the depression. Beside that, in COPD patient has mediator proinflamation are TNF-Î± and IL-6 that can make severe depression. Methods: This study is an observational analytic with cross sectional approach. The subjects are moderate to severe persistent asthma and moderate to severe Chronic Ostructive Pulmonary Disease (COPD) who came to pulmonary medicine clinic of Dr. Moewardi Hospital on April until June 2013. Subject were selected through purposive sampling. The study data obtained by doing interview qoestionnaire Beck Depression Inventory II (BDI-II). The data were analyze by t-test through SPSS Program 18 for Windows. Results: Data from 39 subjects consisting of 21 moderate to severe persistent asthma patients and 18 moderate to severe COPD patients. Median score of BDI-II moderate to severe COPD (11.89) is higher than moderate to severe persistent asthma (8.71). Data was also analyze by t-test by the significance p = 0.062. Conclusion: The study suggested no significant differences of depression between moderate to severe persistent asthma and moderate to severe COPD in Dr. Moewardi Hospital. Keyword: moderate to severe persistent asthma, moderate to severe COPD, depression. Â